Competitive biosorption and phytotoxicity of chlorophenols in aqueous solution to Canna indica L - Christian Ebere Enyoh; Beniah Obinna Isiuku (Current Research in Green and Sustainable Chemistry, 2021)
In this study, simultaneous adsorption and phytotoxicity of pentachlorophenols (PCP) and trichlorophenol (TCP) were investigated by using single and binary component solutions to Canna indica L. For binary mixtures, the extended Langmuir and Freundlich isotherm models were employed and both models are not suitable for the description of adsorption data in the binary system. These results were attributed to the insensitivity of the models to the competitive and interactive effects in the system. The calculated interactive effect (IE) for the chlorophenols in the binary system showed values greater than one for TCP (1.12) while less than one for PCP (0.89) while the mixture toxicity index was −10.93 indicating an antagonistic effect probably due to the number of moieties on the benzene rings. Thus the entrapment of PCP is suppressed in the presence of TCP. The phytotoxocity tests showed that both PCP and TCP treatments caused chlorosis and necrosis to Canna indica L, which manifested with prolong exposure time and higher concentrations (>100 ​mg/L). Although most treatments showed no significant differences (p ​> ​0.05) except for 250 ​mg/L, the biomass weight of the studied plant reduced with increasing concentrations. Canna indica L. showed higher biomass weight in the treatment of TCP than PCP, which suggests that PCP showed higher toxicity to the plant than TCP. For the effect of binary mixture treatments of PCP and TCP on dry biomass of Canna indica L over 25 days showed that the control had higher biomass weight compared to all other treatments. Overall, the different binary mixture ratios showed significant differences (p ​< ​0.05) from the control. Generally, the relative growth rate and tolerance index dropped with increasing concentrations. Overall, Canna indica L. is either a tolerant plant or can metabolize the chlorophenol to less toxic metabolites. According to this study, Canna indica L. could prove to be a promising low cost phytoremediator for the chlorophenols in aqueous solutions.